Pengaruh Pengunaan Media Sosial Tik-Tok terhadap Karakter Siswa Kelas V Madrasah Ibtidaiyah - Nur Ilahin (IBTIDA, 2022)
Tiktok social media has recently become a trend for young people, especially for the character of elementary school children. This type of research is qualitative research that we conducted in class V MI Banin Banat Siman Lamongan. The data collection technique in this research is using the descriptive method. Documentation data is the character of students, namely obedient attitudes and behavior in carrying out their religious teachings and actions that show orderly behavior and obey various provisions and regulations. Data analysis uses statistical analysis, namely interpretations and conclusions made based on statistical analysis to find out how much influence the use of social media has on the character of students. The results of the study show that there is a significant influence on the use of tiktok social media on the character of students. From the results of preliminary research conducted by analysts, it is obtained that the use of online media tiktok can affect the character of these students. So that this tiktok application-based media is an external factor that affects the character of students. Many of them use online media too often, which makes them sluggish to learn. In addition, it is very disappointing for students' actual learning outcomes the next day.